Calix[4]arene‐Functionalised Silver Nanoparticles as Hosts for Pyridinium‐Loaded Gold Nanoparticles as Guests. Issue 43 (7th September 2015) - Vita, Francesco; Boccia, Alice; Marrani, Andrea G.; Zanoni, Robertino; Rossi, Francesca; Arduini, Arturo; Secchi, Andrea
Abstract A series of lipophilic gold nanoparticles (AuNPs) circa 5 nm in diameter and having a mixed organic layer consisting of 1‐dodecanethiol and 1‐(11‐mercaptoundecyl) pyridinium bromide was synthesised by reacting tetraoctylammonium bromide stabilised AuNPs in toluene with different mixtures of the two thiolate ligands. A bidentate ω‐alkylthiolate calix[4]arene derivative was instead used as a functional protecting layer on AgNPs of approximately 3 nm. The functionalised nanoparticles were characterised by transmission electron microscopy (TEM), and by UV/Vis and X‐ray photoelectron spectroscopy (XPS). Recognition of the pyridinium moieties loaded on the AuNPs by the calix[4]arene units immobilised on the AgNPs was demonstrated in solution of weakly polar solvents by UV/Vis titrations and DLS measurements. The extent of Au‐AgNPs aggregation, shown through the low‐energy shift of their surface plasmon bands (SPB), was strongly dependent on the loading of the pyridinium moieties present in the organic layer of the AuNPs. Extensive aggregation between dodecanethiol‐capped AuNPs and the Ag calix[4]arene‐functionalised NPs was also promoted by the action of a simple N‐octyl pyridinium difunctional supramolecular linker. This linker can interdigitate through its long fatty tail in the organic layer of the dodecanethiol‐capped AuNPs, and simultaneously interact through its pyridinium moiety with the calix[4]arene units at the surface of the modified AgNPs.